Pengujian Jarak dan Waktu Gabung Protokol IEEE 802.15.4 / ZigBee di Lingkungan Indoor - Koko Joni; Risanuri Hidayat; Sujoko Sumaryono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
Protocol IEEE 802.15.4/ZigBee is a standard for low power personal network. This paper discusses about router, end device and coordinator using ZigBee protocol in term of distance and time to join. Testing carried out by pairing and On/Off method that constitute communication model from router or end device to coordinator. The result showed that with pairing methods could far distance until outside building with further distance about 65 meters, while the distance using On/Off method can reach few room in indoor area. Longest time to join need about 1 minute 15 seconds. Compare with pairing method that always connected, On/Off method need more time to connect in ZigBee Network.